Portuguese research on physical education and sport didactics—a critical discussion - Onofre, Marcos; Costa, João; Martins, João; Quitério, Ana; Farias, Cláudio; Mesquita, Isabel (Frontiers in Sports and Active Living, 2023)
This article presents a discussion of research in Physical Education and Sport Didactics in Portugal. It starts by situating it from an historical perspective, placing the 1980s as the beginning era, mainly based on the studies provided by the two first Physical Education higher education institutes of the country. The initial research, first based on master and doctoral dissertations, progressed to ongoing projects that have been disseminated in international and national journals and books. This development is also reported from the theoretical, conceptual, and methodological perspectives, showing how it has informed the quality of Physical Education and teacher education as the two main research strands to be described, however, acknowledging that a strand on sports coaching and coach education exists. On teaching Physical Education, the article discusses the elements relative to the teacher and to the student, focusing from the immediate and short-term to the distant and long-term events that lead into young adulthood's active lifestyles. In this analysis, research on curriculum and assessment are also reported. On physical education teacher education, the article shows the prevalence of the post-primary Physical Education to argue for the need for more research on primary-level education, and discusses the diverse foci from initial teacher education to in-service education practises. In line with current trends in research, we suggest a set of four features for the future research agenda: (1) addressing short to long-term outcomes of Physical Education; (2) adopting multifactorial and multi-layered perspectives of analysis; (3) embracing inter- and multidisciplinary designs; and (4) taking comparative perspectives within and between European countries, and between Europe and other continents. We conclude that these features need to focus on four levels of integration and cooperation: (a) integration between the research initiatives and the needs of the professional field; (b) integration between research on teaching and learning, teacher education and the curriculum; (c) cooperation between the different national higher education and professional institutions; and (d) integration in the international research agenda by leading and participating in project partnerships which are needed to fully and effectively implement such agenda.